Renal denervation: mechanisms and clinical aspects - Heradien, Marshall J; van der Bijl, Pieter; Brink, Paul A (African Journal of Nephrology, 2020)
Hypertension is a global health issue of paramount importance, which has not spared the African continent where an unacceptably high prevalence of uncontrolled blood pressure prevails among its population. Renal denervation (RD) represents an invasive management option for resistant hypertension, acting via several different physiological pathways – mostly predicated on modification of the renal autonomic nervous system. The evidence base for RD has recently been expanded by three randomised, sham-controlled clinical trials, which demonstrated significant blood pressure reductions under a variety of clinical conditions. In this review, both the renal mechanisms underlying RD, as well as the clinical aspects of its application to hypertension, are discussed.